Sequential Administration of PCV13 Followed by PPSV23 Results in a More Robust Immune Response in PPSV23-Naïve Adults Age 60–64 Years. (4th October 2017) - Chilson, Erica; Atkinson, Bruce; Hall-Murray, Cassandra; Snow, Vincenza; Schmoele-Thoma, Beate; Isturiz, Raúl E; Scott, Daniel A
Abstract: Background: Recommendations for adult pneumococcal immunization generally specify the use of PCV13 first, followed by PPSV23, when administered sequentially, for prevention of pneumococcal disease. This is supported by observations of reduced functional opsonophagocytic assay (OPA) antibody titers in subjects who received PPSV23 first compared with PCV13 first. Methods: In a previously-published phase 3 study of pneumococcal vaccine–naïve adults 60–64 years of age, participants received PCV13 followed by PPSV23 one year later (PCV13/PPSV23) or PPSV23 followed by PCV13 one year later (PPSV23/PCV13). Here we report the previously unpublished clinically relevant comparisons for the 2 sequential dosing groups by showing the antibody response curve analyses by serotype. We also highlight the reverse cumulative distribution curve (RCDC) analysis by serotype for the 2 relevant sequential dosing groups. Results: OPA titers for shared serotypes rose substantially from pre-vaccination to 1 month post-initial vaccination for both groups. For all serotypes, OPA titers declined over the year interval between vaccinations, but remained higher at the pre-vaccination 2 time point compared with baseline for both groups. When evaluating the antibody response curves, the OPA geometric mean titers (GMTs) were generally higher for all shared serotypes at all measured time points in the PCV13/PPSV23 group compared with the PPSV23/PCV13 group; example serotype 19F (Figure 1). RCDC analyses show that for the PCV13/PPSV23 group, OPA titers after vaccination 2 were generally higher across the full range of responses than for PPSV23/PCV13; example serotype 19F (Figure 2). Conclusion: The observed immune responses, with the sequential administration of PCV13 followed by PPSV23 one year later (PCV13/PPSV23), are higher compared with responses observed with PPSV23 followed by PCV13 one year later (PPSV23/PCV13). This supports the administration of PCV13 first when use of both pneumococcal vaccines is appropriate. Limitations: This study was not designed to determine the optimal interval between PCV13 and PPSV23 doses. Disclosures: E. Chilson, Pfizer Inc: Employee and Shareholder, Salary; B. Atkinson, Pfizer Inc: Shareholder, Salary; C. Hall-Murray, Pfizer, Inc.: Employee and Shareholder, Salary; V. Snow, Pfizer Inc: Employee and Shareholder, Salary; B. Schmoele-Thoma, Pfizer Inc: Shareholder, Salary; R. E. Isturiz, Pfizer, Inc.: Employee, Salary; D. A. Scott, Pfizer Inc: Shareholder, Salary